2012
DOI: 10.1016/j.freeradbiomed.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β suppresses glutamate–cysteine ligase gene expression and induces oxidative stress in a lung fibrosis model

Abstract: The concentration of glutathione (GSH), the most abundant intracellular free thiol and an important antioxidant, is decreased in the lung in both fibrotic diseases and experimental fibrosis models. The underlying mechanisms and biological significance of GSH depletion, however, remain unclear. Transforming growth factor beta (TGF-β) is the most potent and ubiquitous profibrogenic cytokine and its expression is increased in almost all fibrotic diseases. In this study, we show that increasing TGF-β1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 60 publications
2
68
0
3
Order By: Relevance
“…including lung fibrosis and idiopathic pulmonary fibrosis. The activation of TGF-β1 expression induces fibroblasts to synthesize and contract the extracellular matrix (29,30). We found that maternal LPS treatment and/or postnatal hyperoxia increased total collagen content and the level of TGF-β1 expression in lung tissues, compared with those of the control pups.…”
Section: Discussionmentioning
confidence: 71%
“…including lung fibrosis and idiopathic pulmonary fibrosis. The activation of TGF-β1 expression induces fibroblasts to synthesize and contract the extracellular matrix (29,30). We found that maternal LPS treatment and/or postnatal hyperoxia increased total collagen content and the level of TGF-β1 expression in lung tissues, compared with those of the control pups.…”
Section: Discussionmentioning
confidence: 71%
“…To further confirm that the augmented glycolysis does occur during lung fibrosis, we used another wellrecognized model in that mice were intratracheally administered adenovirus that express constitutively active TGF-b1 (Ad-TGF-b1 223/225 ) (19). As shown in Figure 1I, there were significantly greater levels of lactate in the lungs of mice that received TGF-b1-expressing adenovirus.…”
Section: Lung Myo-fbs and Fibrotic Lungs Demonstrate Augmented Glycolmentioning
confidence: 93%
“…The bleomycin and TGF-b1-induced lung fibrosis models were described previously (19,20) and detailed in the online supplement METHODS. The animal protocol was approved by the University of Alabama Birmingham Institutional Animal Care and Use Committee.…”
Section: Experimental Pulmonary Fibrosis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these two subunits, TGF-β1 has been shown to down-regulate the expression of gamma-GCSh in the fibrotic areas of interstitial pneumonia (Tiitto et al 2004) and in human lung alveolar epithelial cells (Liu et al 2012). The reduction of gamma-GCSh expression and GSH generation in response to TGF-β1 is also in agreement with the increased protein oxidation and lipid peroxidation in mice with lung fibrosis (Liu et al 2012). All in all, TGF-β1-mediated reduction in GSH production might contribute to oxidative stress during the fibrotic process.…”
Section: Ros and Tgf-β Are Interlinked By Feed-forward And Feedback Mmentioning
confidence: 99%